Comparison of two course books - Drubina Éva (2004)
This thesis is written in methodology. It consists of three main sections. After the introduction the first part of the thesis gives a literature review on general questions, like who needs a course book, how to choose an appropriate book, lists the common problems which usually occur about the textbooks, but now from an author's point of view. The following unit is a survey. It analyses the result of a survey that was based on a questionnaire about what is a good course book like. Experienced English teachers were asked for ranking ten criteria according to their importance. They had to decide which one is the most and which is the least significant for them when they choose a new textbook. The last main section is a comparison, a pre-use evaluation of two course books from a teacher's point of view who is before choosing the appropriate book for her course and is interested in whether an old book would be relevant compared with a modern one. The final outcome is summarised in the Conclusion part of the thesis.